2015
DOI: 10.1002/bip.22656
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vitro antioxidant activities of 6‐amino‐6‐deoxychitosan and its sulfonated derivatives

Abstract: The 6-amino-6-deoxychitosan (NC) and their 2, 6-di-N-sulfonated derivatives were prepared via N-phthaloylation, tosylation, azidation, hydrazinolysis, reduction of azide groups and N-sulfonation, and their structures were systematically characterized by FT-IR, 2D HSQC NMR, XRD, gel permeation chromatography (GPC), and elemental analysis. The 6-amino-6-deoxychitosan showed effect in three selected antioxidant essays, including reducing power, superoxide anion radical scavenging ability, and hydroxyl radical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Meanwhile, the results showed that aminofunctionalized chitosan derivative 7b exhibited the stronger antioxidant properties than hydroxyl-modified chitosan derivative 7a, which should be attributed to the appearance of eNH 2 group as a stronger hydrogen donor than eOH group. This result was in agreement with the reports of Luan et al (2018) and Yang et al (2015), in which they found that the antioxidant activities of chitosan derivatives had improved significantly after the introduction of amino group by substitution of hydroxyl group at C-6 on chitosan backbones. Moreover, because of the incorporation of 1,2,3-triazole in the present study, a higher scavenging rate against DPPH radical and a stronger reducing power at 0.4 mg/mL of amino-functionalized chitosan 7b were observed compared with that of 6-amino-6-deoxy chitosan at the same concentration reported early by our group (Luan et al, 2018).…”
Section: Reducing Powersupporting
confidence: 93%
“…Meanwhile, the results showed that aminofunctionalized chitosan derivative 7b exhibited the stronger antioxidant properties than hydroxyl-modified chitosan derivative 7a, which should be attributed to the appearance of eNH 2 group as a stronger hydrogen donor than eOH group. This result was in agreement with the reports of Luan et al (2018) and Yang et al (2015), in which they found that the antioxidant activities of chitosan derivatives had improved significantly after the introduction of amino group by substitution of hydroxyl group at C-6 on chitosan backbones. Moreover, because of the incorporation of 1,2,3-triazole in the present study, a higher scavenging rate against DPPH radical and a stronger reducing power at 0.4 mg/mL of amino-functionalized chitosan 7b were observed compared with that of 6-amino-6-deoxy chitosan at the same concentration reported early by our group (Luan et al, 2018).…”
Section: Reducing Powersupporting
confidence: 93%
“…Chitosan is one of the most abundant natural polysaccharides and its antifungal activity against various groups of pathogenic fungi has drawn a lot of attention [ 9 ]. As the only alkaline polysaccharide in nature, chitosan is mainly obtained via the deacetylation of chitin under alkaline conditions [ 10 , 11 , 12 ]. The main chain of chitosan is mainly composed of glucosamine and N -acetylglucosamine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the width of X-ray diffraction peak is related to the size of crystallite and the broadened peak usually results from small crystallite [ 32 ]. In addition, weaker peak implies that there is more amorphous phase in the matrix.…”
Section: Resultsmentioning
confidence: 99%